Analysis Methods for Development of Standard Reference Material (SRM) Zircon Minerals Synthesis - Samin Samin; Susanna Tuning Sunanti (Indonesian Journal of Chemistry, 2018)
The synthesis method of in-house zircon minerals certified reference material (CRM) from Kalimantan (Tumbang Titi), and Bangka has been studied with statistical method of ISO 13528-2008 and ISO 35-2006. Zircon Minerals weighing of 10 kg, and it was dried at 90 °C for 2 × 6 h in a closed room, then crushed with a Ball-Mill up to passes 200 mesh, and homogenized in a homogenizer for 3 × 6 h. The water content in zircon minerals powder is tested by gravimetric method, whereas the homogeneity and stability assessed by statistical methods. Zircon mineral powders are distributed to seven accredited testing laboratory for testing the composition and content of the oxides with the validated analytical methods. Standardization and characterization of candidate zircon mineral certified reference materials are done by using XRD (X-Ray Diffraction) and used standard materials of JCRM R 502 from Japan. The test results of oxide concentrations from various laboratories processed with statistical methods. From the data by test laboratories obtained 40 bottles of the prototype in-house certified reference materials zircon mineral powders from Kalimantan and Bangka with a capacity of 100 g. Based on standardization and characterization test data obtained a major chemical compound on zircon minerals Kalimantan and Bangka similar to the standard that is ZrSiO4. This in-house CRM is traced to certified reference materials from Japan (JCRM-502).